The effects of citral on the intestinal health and growth performance of American bullfrogs (Aquarana catesbeiana) - Xiaoting Zheng; Qiuyu Chen; Xueying Liang; Jingyi Xie; Alfredo Loor; Hongbiao Dong; Jinlong Yang; Jiasong Zhang (BMC Veterinary Research)
Abstract Bullfrogs (Aquarana catesbeiana) are increasingly cultivated for their high nutritional value and adaptability to intensive aquaculture systems. However, ensuring optimal intestinal health and growth performance remains a challenge due to poor water quality and high stocking densities. This study evaluated the effects of varying dietary concentrations of citral, a natural compound from lemongrass essential oil, on the intestinal health, microbiota, antioxidant capacity, and growth performance of juvenile bullfrogs. A total of 200 juvenile bullfrogs (initial weight 6.85 ± 0.71 g) were randomly assigned into six groups, each receiving diets supplemented with citral at 0, 1, 2, 4, 8, and 16 mL/kg feed for 8 weeks. Citral supplementation significantly improved intestinal morphology, with goblet cell numbers, mucosal thickness, and villus-to-crypt ratios peaking at 2–4 mL/kg (P < 0.05). Optimal doses of 2–4 mL/kg also enhanced digestive enzyme activities, with α-amylase, lipase, and pepsin activities showing significant increases compared to the control group (P < 0.05). Antioxidant markers, including total antioxidant capacity (T-AOC) and glutathione (GSH), were highest at 2 mL/kg, while higher citral concentrations reduced superoxide dismutase (SOD) and catalase (CAT) activities, indicating potential oxidative stress at 8–16 mL/kg (P < 0.05). Citral also modulated the intestinal microbiota, increasing the relative abundance of beneficial bacteria such as Cetobacterium at 1–2 mL/kg (P < 0.05). However, microbial diversity decreased significantly at concentrations above 4 mL/kg. Growth performance analysis revealed that 4 mL/kg citral supplementation significantly improved weight gain rate (WGR), specific growth rate (SGR), carcass weight (CW), and feed efficiency (FE), while survival rates declined at 16 mL/kg (P < 0.05). A linear regression model determined the optimal dietary citral concentration to be 3.216–3.942 mL/kg. This study concludes that dietary citral at 2–4 mL/kg optimally enhances growth performance, intestinal health, and antioxidant capacity in juvenile bullfrogs, while higher concentrations may disrupt gut health and oxidative balance. These findings provide valuable insights into the use of natural compounds like citral for sustainable aquaculture practices.